التسامح اللساني في الحضارة العربية والإسلامية: ابن حزم الأندلسي والبيروني أنموذجا - بوعبدالله، لعبيدي محمد (جامعة القاهرة - كلية الآداب, 2023)
لا شك أن الحضارة العربية والإسلامية قد عرفت تنوعا لسانيا، من خلال الانفتاح على الآخر، مما أفرز إقامة حوار حضاري راق كانت إحدى وسائله الترجمة والنقل. وقد بدا هذا جليا خلال القرنين الرابع والخامس الهجريين، في بذل العلماء كل طاقاتهم وسعيهم الحثيث من أجل نقل العلوم وترجمة المفاهيم من عدة لغات إلى العربية، وأعقب ذلك إبداع علمي وتميز معرفي في مختلف العلوم والمعارف والفنون. ويتنزل هذا الانفتاح ضمن منظومة فكرية ودينية، نتجت من كون التنوع اللغوي واختلاف الألسن آية من الآيات الكونية، والتسامح اللساني ملمحا إنسانيا، حيث أرسل الله سبحانه الرسل إلى أقوامهم بلسانهم؛ لتحقيق إحدى أهم الوظائف الرسالية التواصلية وهي الوظيفة البيانية. وفي هذا الصدد يحاول البحث-بمنهج وصفي تحليلي- في استجلاء مظاهر التسامح اللساني من خلال النقاط الثلاث الآتية: أولاً-التسامح اللساني في القرآن الكريم: من خلال إبراز نماذج من عدة وضعيات تخاطبية أهمها بين الأنبياء وأقوامهم؛ تهدف جميعها إلى تحقيق الوظيفة البيانية، وتبرز مدى الترابط الأخوي بينهم. ثانيا- التسامح اللساني في السيرة النبوية: وفي موقفه صلى الله عليه وسلم وموقف أصحابه منه. ثالثا التسامح اللساني في الخطاب العلمي قديما: ونعرض فيه نماذج من مواقف علمائنا قديما في مجال التسامح اللساني تنظيرا وممارسة، فمن المنظرين للتسامح اللساني ابن حزم، وممن مارسوا هذا المفهوم الراقي أبو الريحان البيروني، ما جعل هؤلاء يقدمون الصورة المشرقة والمشرفة عن حضارة أسهمت في البناء الفكري والعلمي للإنسانية. There is no doubt that the Arabic & Islamic civilization has known linguistic diversity through openness to the other, which has resulted in the establishment of a sophisticated civilized dialogue, one of which was translation and transmission. This was evident during the 4th and 5th centuries AH, when scholars exerted all their energies and strived to transfer science and translate concepts from several languages into Arabic, and this was followed by scientific creativity and cognitive distinction in various sciences, knowledge and arts. This openness is falls within an intellectual and religious system that makes the linguistic diversity and the difference of languages one of the cosmic signs, and linguistic tolerance a human appearance, where every messenger sent by God to his people with their languages. To achieve one of the most important mission and communicative functions, which is the demonstration function. In this regard, this research falls, which attempts through a descriptive and analytical approach -to elucidate the manifestations of linguistic tolerance through the following three points: 1st: Linguistic tolerance in the Qur’an: by highlighting examples of several discursive situations, the most important of which are between the prophets and their people. All of them aim to achieve the demonstration function, and highlight the extent of fraternal bonding between them. 2nd: Linguistic tolerance in the position of Prophet Muhammad and the position of his companions on the multilingualism. 3rd: Linguistic tolerance in ancient scientific thinking and discourse: In it, we present examples of the positions of our scholars in the past in the field of linguistic tolerance in theory and practice. Among the theorists ᵓibnu ḥazm, and those who used this sophisticated concept, ᵓal-bayrūnī, which made them present a bright and honorable picture of a civilization that contributed to the intellectual and scientific construction of humanity.
Keywords: التنوع اللغوي -- التسامح اللساني -- السيرة النبوية -- الحضارة العربية